ChemInform Abstract: Phase Transitions and Nucleation Mechanisms in Metals Studied by Nanocalorimetry: A Review. Issue 36 (September 2015) - Zhao, Bingge; Li, Linfang; Lu, Fenggui; Zhai, Qijie; Yang, Bin; Schick, Christoph; Gao, Yulai
Abstract Review: 102 refs.